Nase skúsenosti s redukcnou mamaplastikou podĺa Lemperleho - Hudáková, J; Guzanin, S; Kacmár, P; Jabur, V; Sabovcík, R (Rozhledy v chirurgii, 2000)
The authors describe their experience with Lemperle's method of reduction mammoplasty. It is based on the procedure of Wise and Strombeck and involves resection of the lower quadrants. We used this operation in seventy patients of the age between seventeen and 55 years during last five years. Six of our cases (8.6%) were classified as gigantomasty, four of them (5.7%) as hypertrophy with asymmetry and sixty patients (85.7%) were classified as hypertrophy with ptosis. As to the postoperative complications, two patients (2.8%) developed partial necrosis of the areola with dehiscence of the vertical suture and one patient (1.4%) partial dehiscence of the vertical suture. The resected tissue volumes were between 4,500 g and 400 g. The patients were very pleased with the result of the operation.
Keywords: Mammaplasty; Middle Aged; ženské pohlaví; dospělí; Humans; Adult; mamoplastika; Female; Adolescent; lidé; mladiství; lidé středního věku